Characterization of the complete mitochondrial genome of the Huanhu Yak (Bos Grunniens). Issue 1 (2nd January 2019) - Wu, Xiaoyun; Zhou, Xuelan; Ding, Xuezhi; Liang, Chunian; Guo, Xian; Chu, Min; Wang, Hongbo; Pei, Jie; Bao, Pengjia; Yan, Ping
Abstract: Huanhu yak is a native yak species of China. In the present study, we reported the complete mitochondrial DNA sequence of the Huanhu yak. The complete mitochondrial genome is a circular molecule with 16, 323 bp length which consisted of 13 protein-coding genes, 22 tRNA genes, 2 ribosomal RNA genes, and a non-coding control region (D-loop region). The overall nucleotide composition is 33.71% A, 27.26% T, 25.82% C, and 13.21% G, respectively. The phylogenetic analysis showed that the genetic relationship of Huanhu yak is closer to Pali yak.